Comparative evaluation of soil loss in the biological corridor between the Purace National park and the guacharos cave in Huila - Agudelo Perdomo, Camilo Augusto
The purpose of the research was to evaluate soil loss in experimental plots in the Biological Corridor between National Parks Purace and the Cave of the Guacharos in the department of Huila in crops with traditional management versus alternative management; results that were validated by the Universal Soil Loss Equation. Measurement of soil loss was performed and the rains were registered over a period of four months, qualifying the rainy season as mild, resulting in increased erosion in growing conventional coffee (1.14 t ha-1. year-1), followed by conventional blackberry (0.99 t ha-1.year-1) with significant differences attributed to management of coverage. In crops with tillage practices there were minor losses (0.37 t ha-1.year-1) compared to the conventional management (0.53 t ha-1.year-1), the latter include burning, removal of surface coverage and soil movement. In treatments with ranching and semi-stabled no significant differences were found in soil erosion. There is no significant correlation between soil losses USLE estimated and measures in runoff plots.  Para citar este artículoAgudelo, C., Torrente, A. y Vargas, A. (2015). Evaluación comparativa de pérdidas de suelo en el corredor biológico entre parques nacionales Puracé y Cueva de los Guácharos en el Huila. Rev. Colomb. Investig. Agroindustriales, 2(1), 41-52. DOI: http://dx.doi.org/10.23850/24220582.168